2017
DOI: 10.1210/en.2017-00205
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Inhibition of DNA Methylation Alters Cell Phenotype in Sexually Dimorphic Regions of the Mouse Brain

Abstract: Many of the best-studied neural sex differences relate to differences in cell number and are due to the hormonal control of developmental cell death. However, several prominent neural sex differences persist even if cell death is eliminated. We hypothesized that these may reflect cell phenotype "decisions" that depend on epigenetic mechanisms, such as DNA methylation. To test this, we treated newborn mice with the DNA methyltransferase (DNMT) inhibitor zebularine, or vehicle, and examined two sexually dimorphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 50 publications
2
32
0
Order By: Relevance
“…Neonatal inhibition of DNA methylation increased ERα cell density eight‐fold in males and completely eliminated the sex difference (Figure ). A similar pattern was seen in the mPOA . This suggests that the sex differences in ERα in the VMHvl and mPOA depend on differential DNA methylation in males and females.…”
Section: The Presentsupporting
confidence: 70%
See 2 more Smart Citations
“…Neonatal inhibition of DNA methylation increased ERα cell density eight‐fold in males and completely eliminated the sex difference (Figure ). A similar pattern was seen in the mPOA . This suggests that the sex differences in ERα in the VMHvl and mPOA depend on differential DNA methylation in males and females.…”
Section: The Presentsupporting
confidence: 70%
“…A sex difference in the opposite direction (male>female) is seen for calbindin‐expressing cells in the mPOA. We found that neonatally inhibiting DNA methylation significantly increased the number of calbindin‐expressing cells several weeks later, and did so in both sexes . Thus, within the same animal, neonatal DNMT inhibition feminised some cell groups (ERα in VMH and mPOA of males) and made other cell groups more male‐like (calbindin in the mPOA).…”
Section: The Presentmentioning
confidence: 65%
See 1 more Smart Citation
“…Recent work by Forger’s group showed that pharmacological inhibition of DNA methyltransferase activity at birth feminized expression of Esr1, a nuclear hormone receptor for estrogen, in two hypothalamic nuclei [41•]. This suggests that DNA methylation may establish or maintain male-specific gene repression in these regions.…”
Section: Sexual Differentiation Of the Mouse Brain: Emerging Evidencementioning
confidence: 99%
“…In mice, the organizational effects of T results in striking and delayed brain methylome and transcriptomic effects (Ghahramani et al 2014), suggesting that critical windows of exposure to NED might be even more prolonged that originally envisioned. Recently, Mosley et al (2017) reported in mice that neonatal treatment with a DNA methyltransferase (DNMT) inhibitor, zebularine, increased the number of calbindin-D28K (CALB) cell number in the medial preoptic area (mPOA) in both sexes and resulted in greater ESR1 cell density in the ventrolateral portion of the ventromedial nucleus of the hypothalamus (VMHvl) and mPOA. This latter zebularine affect thus abolished sex differences in ESR1 expression observed otherwise in control individuals.…”
Section: Introductionmentioning
confidence: 99%